2021
DOI: 10.1061/(asce)me.1943-5479.0000957
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Analysis of COVID-19 Response Guidelines at Construction Sites in South Korea Using CYCLONE in Terms of Cost and Time

Abstract: The emergence of the coronavirus disease 2019 (COVID-19) pandemic has led to a cost and time crisis for most construction projects around the world. Adherence to COVID-19 response guidelines for construction sites may prevent the occurrence of COVID-19 cases, which eliminates the risk of site closure. However, adding a disinfection process to the construction process, as mandated in COVID-19 response guidelines, increases overall construction cost and time. Conversely, however, not adding a disinfection proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Kim et al [37] published work with scenario-based simulations. They developed three scenarios of curtain-wall operations and measured workdays, calendar days, total cost, and liquidated damages, which included the quantified effect of COVID-19 on pre-and post-COVID-19 curtain-wall operations.…”
Section: Previous Research Work: the Impact Of Covid-19 On Constructionmentioning
confidence: 99%
“…Kim et al [37] published work with scenario-based simulations. They developed three scenarios of curtain-wall operations and measured workdays, calendar days, total cost, and liquidated damages, which included the quantified effect of COVID-19 on pre-and post-COVID-19 curtain-wall operations.…”
Section: Previous Research Work: the Impact Of Covid-19 On Constructionmentioning
confidence: 99%
“…The second group of these studies examined the implications (e.g., legal disputes and delays) of construction disruptions (e.g., Salami et al 2021;Kim et al 2021) and the emergent construction practices as a result of the pandemic (e.g., Simpeh and Amoah 2021;Assaad and El-adaway 2021). For example, Salami et al (2021) explored the measures that construction organizations put in place to mitigate the risks of litigation associated with the contract breaches due to the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Salami et al (2021) explored the measures that construction organizations put in place to mitigate the risks of litigation associated with the contract breaches due to the pandemic. In order to help project owners and contractor respond to the damages caused by the pandemic, Kim et al (2021) proposed a method to estimate the construction cost and schedule before and after the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Al-Mhdawi et al (2020) identified the impact of COVID-19 on construction projects in Iraq [ 10 ], while Jeon et al (2022) proposed the Purdue Index to assess the impact of COVID-19 on the US construction industry [ 6 ]. Other studies explored the response strategies on pandemic impacts [ 13 , 14 , 15 , 16 , 17 , 18 ]. For example, Zamani et al (2022) provided pandemic response strategies in the construction industry for the government [ 13 ], while Kim et al (2021) proposed an approach to examining the feasibility of pandemic guidelines implemented on construction sites in South Korea [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies explored the response strategies on pandemic impacts [ 13 , 14 , 15 , 16 , 17 , 18 ]. For example, Zamani et al (2022) provided pandemic response strategies in the construction industry for the government [ 13 ], while Kim et al (2021) proposed an approach to examining the feasibility of pandemic guidelines implemented on construction sites in South Korea [ 14 ]. However, these studies primarily focused on the economic, financial, and operational consequences of the COVID-19 pandemic, such as reduced productivity and disruptions in the supply chain, while the research on workers occupational health and safety during the pandemic is still lacking, and also given that we know little about how construction workers perceive their work stressors.…”
Section: Introductionmentioning
confidence: 99%